Comprehensive assessment of high-speed passenger trains circulation on the existing railway infrastructure in the Siberian Federal District - E. V. Klimova (Вестник Научно-исследовательского института железнодорожного транспорта)
Introduction. Reducing passenger journey duration at the current stage of transport development is a prerequisite for high-quality passenger service giving railways higher competitive advantage. In order to avoid significant investments, Russian Railways opted to develop mixed high-speed train traffic on the existing infrastructure. The author considered an existing double-track section of mainline railway transport with high-speed passenger train traffic. The research focuses on the effects of putting high-speed passenger trains into circulation on the existing railway infrastructure. The solution to the problem requires a formalised and adapted methodological toolkit for assessing the resulting effects from the introduction of high-speed passenger trains into circulation.Materials and methods. The effects of putting high-speed passenger trains into circulation were assessed using the theory of train traffic control, economic efficiency indicators and the calculation of a specific indicator expressing the ratio of the absolute economic criterion under consideration to the reduction in journey time. The researcher used formulas to calculate performance and cost metrics adapted to the challenges of high-speed passenger traffic on the existing railway infrastructure. Results. The author considered the conditional railway direction O–H chosen as the object of approbation of the developed toolkit and obtained the values of effects from the introduction of high-speed passenger trains for passengers, infrastructure owner and carriers.Discussion and conclusion. This toolkit, after some adaptation, may be used for calculations for railway lines with different equipment (single-track and multiple-track lines) under mixed traffic conditions (passenger and goods trains of different categories, as well as high-speed passenger trains). The results obtained for the O–H direction allow to assess and understand the multifaceted effects arising from the introduction of high-speed trains into circulation on the existing double-track railway infrastructure.